Colchicine and diabetes in patients with chronic coronary artery disease: insights from the LoDoCo2 randomized controlled trial - Mohammadnia, Niekbachsh; Los, Jan; Opstal, Tjerk S. J.; Fiolet, Aernoud T. L.; Eikelboom, John W.; Mosterd, Arend; Nidorf, Stefan M.; Budgeon, Charley A.; Tijssen, Jan G. P.; Thompson, Peter L.; Tack, Cees J.; Simsek, Suat; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Despite optimal treatment, patients with chronic coronary artery disease (CAD) and DM are at high risk of cardiovascular events, underscoring the need for new treatment options. The Low-Dose Colchicine 2 trial showed that colchicine reduces cardiovascular risk in patients with chronic CAD. The objective of this analysis was to determine the efficacy of colchicine in patients with chronic CAD and DM as well as the effect of colchicine on the development of new-onset type 2 diabetes (T2DM).The LoDoCo2 trial randomized 5522 to placebo or colchicine 0.5mg daily, with a median follow-up of 28.6 months. The primary composite endpoint was: cardiovascular death, spontaneous myocardial infarction, ischemic stroke, or ischemia-driven revascularization. The treatment effect in patients with and without DM was evaluated by including an interaction term in the model.In total, 1007 participants (18.2%) had T2DM at baseline. The adjusted hazard ratio (HR, 95% CI) for the primary endpoint in the T2DM group was 1.52 (1.15-2.01, p<0.01) compared to the group without T2DM. The HR for the treatment effect on the primary endpoint was 0.87 (0.61-1.25) in those with T2DM and 0.64 (0.51-0.80) in those without diabetes (pinteraction=0.14). The incidence of new-onset T2DM was 1.5% (34/2270) in the colchicine group and 2.2% (49/2245) in the placebo group (p=0.10).In conclusion, based on the current evidence, the beneficial effects of colchicine on cardiovascular endpoints are consistent regardless of DM status. The potential benefits of colchicine in preventing new-onset DM merit further investigation. These findings are only hypothesis generating and requires larger prospective trials to confirm.